2012
DOI: 10.14419/ijbas.v1i4.292
|View full text |Cite
|
Sign up to set email alerts
|

Influence of silane content on the optical properties of sol gel derived spin coated silica thin films

Abstract: Sol gel technique in combination with spin coating method was utilized for the synthesis of silica thin films. Tetraethyl orthosilicate (TEOS) alkoxide silane precursor was used for one step synthesis of silica sol with 0.1M HCL as a catalyst. Casting solution of silica sol was spin coated on glass substrate. The X-ray diffraction pattern revealed that the sample possesses amorphous silica matrix. Thin films were characterized by Fourier transform infrared spectroscopy (FTIR) and UV-Visible spectroscopy techni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…The silica-based xerogel was characterized by XRD analysis, as reported in Figure 2 . The dried material after two hours at 70 °C showed a broadened peak in the 2θ range of 8–15°; the feature corresponds to the amorphous silica matrix [ 21 ]. The results indicated that no crystalline phase was formed during the initial drying of thin films prepared with TEOS at low temperature.…”
Section: Resultsmentioning
confidence: 99%
“…The silica-based xerogel was characterized by XRD analysis, as reported in Figure 2 . The dried material after two hours at 70 °C showed a broadened peak in the 2θ range of 8–15°; the feature corresponds to the amorphous silica matrix [ 21 ]. The results indicated that no crystalline phase was formed during the initial drying of thin films prepared with TEOS at low temperature.…”
Section: Resultsmentioning
confidence: 99%
“…Figure 2 shows the infrared spectra of the different MMA-SiO2 hybrids. It can be observed absorption band of Si-O-Si at 1070 cm -1 was due to the formation of the silica structure [24]. The shift in the C=O band, 1734 cm -1 , is due to the presence of hydrogen bonds in the system.…”
Section: Chemical and Morphological Characterizationmentioning
confidence: 92%
“…Porous nanomaterials retain native conformation and reactivity of biomolecules. The greater optical transparency makes it valuable in the application of biosensor for medical diagnosis [38].…”
Section: Graphene Oxide (Go)mentioning
confidence: 99%